The Gale encyclopedia of cancer : a guide to cancer and its treatments. - Longe, Jacqueline L. (Gale virtual reference library, 2010)
Comprehensive survey of 120 cancers, cancer drugs, traditional and alternative treatments, side effects and diagnostic procedures.